Biodegradación de xantano por Bacillus pumilus - Gimenez, Juliana Belen (2018)
Xanthan gum is used in the oil industry for the tertiary extraction of petroleum. In its use in the basin of the Gulf of San Jorge, there were problems with the loss of gum structure. Strain identified by Bacillus pumilus was isolated from oil water industry and was grown in the medium with xanthan as carbon source. This change modifies the viscosity of the gum and thus changing its properties.